Signaling pathways in squamous cancer - Glick, Adam B.; Waes, Carter Van.; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Squamous epithelia form the essential lining surface of tissues in contact with the environment, including the skin, and mucosa of the oral cavity, pharynx, larynx, esophagus, respiratory and genital tracts, and several other specialized tissues. These tissues are at highest risk for exposure to environmental carcinogens such as UV light, tobacco smoke, and infectious agents. Consequently, squamous cell carcinomas that form in these tissues are among the most common human solid tumors, and have high morbidity and mortality. The signaling pathways that regulate epithelial homeostasis and the alterations in these pathways that arise during cancer development share certain features among these different tissue sites. This book brings together timely reviews from experts in the field on mechanisms and signaling pathways such as EGFR, TGF?1, NF?B, PPARs and mTOR/AKT that regulate development of squamous cancer in both human and experimental mouse models, with a focus on how these specific signaling pathways can be utilized as targets for anti-cancer therapy. This comprehensive monograph will be important for researchers wishing to enter the field, for medical students, and for established basic and clinical investigators who would gain from an overview of the field.
Electronic reproduction.
Keywords: Squamous cell carcinoma; Electronic books